Parents’ experience and psychoeducation needs when supporting a young person who self-harms - Krysinska, K; Curtis, S; Lamblin, M; Stefanac, N; Gibson, K; Byrne, S; Thorn, P; Rice, SM; McRoberts, A; Ferrey, A; Perry, Y; Lin, A; et al. (MDPI, 2020)
Background Self-harm in young people can have a substantial negative impact on the well-being and functioning of parents and other carers. The “Coping with Self-Harm” booklet was originally developed in the UK as a resource for parents and carers of young people who self-harm, and an adaptation study of this resource was conducted in Australia. This paper presents qualitative analysis of interviews with parents about their experiences and psychoeducational needs when supporting a young person who engages in self harm.